Water-based composite coating with X / gamma ray attenuation performance and preparation method thereof

By combining core-shell structure radiation-proof fillers with water-based polyurethane emulsions, the compatibility and environmental pollution problems of polymer-based radiation shielding materials are solved, efficient radiation attenuation and mechanical strength are achieved, and it is suitable for a variety of substrates.

CN120795771APending Publication Date: 2025-10-17ZHEJIANG UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510842164.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-06-23
Publication Date
2025-10-17

AI Technical Summary

Technical Problem

Existing polymer-based radiation shielding materials have problems with poor filler-matrix compatibility, mechanical integrity damage and environmental pollution in attenuating high-energy electromagnetic waves, making it difficult to maintain effective shielding performance in complex radiation environments.

Method used

A core-shell structured radiation-proof filler is combined with an aqueous polyurethane emulsion, and the modified filler is prepared by ethyl orthosilicate-assisted ball milling. The hydrogen bond interaction between the filler and the polyurethane is utilized to achieve high-load uniform dispersion, and the radiation attenuation efficiency is enhanced through multiple reflections at the core-shell interface.

Benefits of technology

The prepared water-based composite coating exhibits excellent radiation attenuation performance, thermal stability and mechanical strength on a variety of substrates. The preparation process is environmentally friendly and pollution-free, and is suitable for complex radiation environments.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120795771A_ABST
    Figure CN120795771A_ABST
Patent Text Reader

Abstract

The invention discloses a water-based composite coating with X / gamma ray attenuation performance and a preparation method thereof. The preparation process of the composite coating comprises the following steps: firstly, preparing a core-shell structure modified anti-radiation filler of a silicon dioxide shell layer through auxiliary ball milling of tetraethoxysilane, and then preparing the water-based composite coating with stable performance by utilizing the hydrogen-bond interaction of the modified anti-radiation filler with water-based polyurethane and polyvinyl alcohol. The composite coating prepared by the invention has good thermal stability and mechanical properties, also has excellent X / gamma ray attenuation performance, and can be used for radiation attenuation of equipment and fabric surfaces.
Need to check novelty before this filing date? Find Prior Art

Description

TECHNICAL FIELD

[0001] The present invention relates to a waterborne composite coating with X / γ-ray attenuation performance and a preparation method thereof BACKGROUND

[0002] Ionizing radiation shielding is an important research direction in modern radiation protection technology, especially in X-ray and γ-ray attenuation applications. As representatives of high-energy electromagnetic waves, X-rays and γ-rays have excellent penetration ability and ionizing effects, and are widely used in medical diagnosis, industrial testing, nuclear energy utilization, space exploration and other fields. However, their non-selective damage to biological tissues has caused significant radiation hazards.

[0003] In theory, elements with high atomic number and high density have superior linear attenuation coefficients and shielding efficiency. Therefore, lead and lead-based compounds have been used as cost-effective mainstream shielding fillers in radiation protection materials. However, the inherent toxicity and high mass density of lead lead to limitations in its application, such as the risk of compression and health risks for humans wearing lead aprons for a long time.

[0004] Current radiation shielding research mainly focuses on developing low-toxicity, lightweight polymer-based shielding materials, usually by adding high-atomic-number (Z) elements such as gadolinium, bismuth, tungsten, barium and tantalum to replace lead. However, the poor compatibility of the filler matrix still poses a challenge to the heterogeneous dispersion of high-Z elements in the composite system. Current research shows that mechanical dispersion techniques, chemical surface modification and the use of porous matrices can effectively enhance interfacial compatibility while maintaining satisfactory radiation attenuation performance. However, achieving high filler loading capacity without compromising mechanical integrity still requires further research in practical applications.

[0005] Polymer-based radiation shielding materials are usually prepared by conventional processing techniques such as injection molding, extrusion and thermoforming. These production schemes are usually energy-intensive processes with environmental problems, involving high temperature and pressure conditions and the use of large amounts of organic solvents. In addition, the inherent radiation resistance of the polymer matrix often limits the degradation caused by radiation and compromises the mechanical integrity in long-term use. If a sprayable radiation shielding coating that can adapt to complex irradiation environments can be developed, not only can the integrity of the substrate be maintained, but also repeated applications can be made to offset the degradation of the polymer matrix, thus effectively solving the problem of low radiation durability of polymer materials. SUMMARY

[0006] The present application aims to provide a water-based composite coating with X / γ-ray attenuation performance and a preparation method thereof. The water-based composite coating with X / γ-ray attenuation performance has good heat resistance, mechanical strength and X / γ-ray attenuation performance. The present application can improve the mechanical properties and X / γ-ray attenuation performance of the water-based composite coating by adding fillers with core-shell structure to the water-based polyurethane emulsion.

[0007] The water-based composite coating with X / γ-ray attenuation performance of the present application utilizes the hydrogen bond interaction between the core-shell structure fillers (the core-shell structure fillers specifically have silica as the shell layer and radiation-proof fillers as the core layer) prepared by tetraethyl orthosilicate assisted ball milling and the water-based polyurethane. The fillers can be uniformly dispersed in the water-based matrix at a high load. The multiple reflections of the rays can occur at the core-shell interface, which is conducive to the collision of photons and high-Z elements, and improves the X / γ-ray attenuation efficiency.

[0008] The preparation method is as follows: dispersing the radiation-proof fillers by ultrasonic dispersion, and then ball milling for 6 hours with the assistance of tetraethyl orthosilicate. After the ball milling, the product is washed by centrifugation with anhydrous ethanol for three times. Finally, the modified radiation-proof fillers are dried in a vacuum oven at 60°C for 12 hours to obtain the modified radiation-proof fillers. The modified radiation-proof fillers are added to the polyvinyl alcohol aqueous solution, and ultrasonic stirring is performed for 20 minutes to obtain a smooth and uniform slurry. Then, the water-based polyurethane emulsion prepared in advance is added to the slurry, vacuum defoaming treatment is performed after stirring for 30 minutes, and finally drying is performed to obtain the water-based composite coating.

[0009] Specifically,

[0010] 1) The radiation-proof fillers are dispersed in a mixed solution of ethanol and water, ammonia water is added to adjust the pH, and the fillers are uniformly dispersed in the solution under the action of ultrasonic waves for 20 minutes. Then, stirring is performed for 30 minutes, and tetraethyl orthosilicate is added for ball milling for 6 hours. After the ball milling, the product is washed by centrifugation with anhydrous ethanol for three times. Finally, the modified radiation-proof fillers are dried at 60°C for 12 hours.

[0011] 2) Polytetrahydrofuran and isophorone diisocyanate are stirred at 80°C under nitrogen protection for 1 hour; after cooling to 60°C, 2,2-dimethylol butyric acid and 1,4-butanediol are added, and two drops of dibutyltin dilaurate are added dropwise, and the reaction is continued for 4 hours; the reaction system is cooled to 50°C, and then triethylamine is added to neutralize the carboxyl groups on the polymer chain. During the entire reaction process, 20-40% volume fraction of acetone is added to reduce the viscosity of the system. After neutralization for 30 minutes, high-speed stirring is performed under an ice water bath while deionized water is added dropwise, and the stirring is continued for 1 hour. Acetone is removed by rotary evaporation to obtain a water-based polyurethane emulsion.

[0012] 3) The modified anti-radiation particles prepared in step (1) are added to the polyvinyl alcohol aqueous solution prepared in advance, and ultrasonic stirring is performed for 20 min to obtain a smooth and uniform slurry. Then, the water-based polyurethane emulsion prepared in step (2) is added, and stirring is performed for 30 min, followed by vacuum defoaming treatment to obtain a water-based composite coating.

[0013] In the above technical solution, further, the anti-radiation filler in step 1) is at least one of bismuth oxide and gadolinium oxide, the mass ratio of ethanol and water is 16:1, the ammonia water is adjusted to a pH of 10, the mass ratio of the anti-radiation filler to tetraethyl orthosilicate is 15:1-10; the ball milling speed is 400 revolutions per minute, and the ball-to-material ratio is 30:1. In step 2), the molar ratio of isocyanate groups to total hydroxyl groups (hydroxyl groups from polytetrahydrofuran, 2,2-dimethylol butyric acid and 1,4-butanediol) is 1.15-1.25, the mass fraction of 2,2-dimethylol butyric acid in the entire reaction system (i.e., the total mass of polytetrahydrofuran, isophorone diisocyanate, 2,2-dimethylol butyric acid and 1,4-butanediol) is 4.5-5%, the molar ratio of amino groups (from triethylamine) to carboxyl groups (from 2,2-dimethylol butyric acid) is 1:1, and the stirring speed during ice water bath is 600-800 revolutions per minute. In step 3), the mass concentration of the polyvinyl alcohol aqueous solution is 5-7%, the mass fraction of the anti-radiation filler in the water-based composite coating is 7-36%, the mass fraction of the polyvinyl alcohol aqueous solution is 44-48%, and the mass fraction of the water-based polyurethane emulsion is 20-45%.

[0014] The present application has the following advantages:

[0015] 1. The present application uses tetraethyl orthosilicate to assist in the preparation of modified anti-radiation fillers, and utilizes the hydrogen bond interaction between the hydroxyl groups on the surface of the modified anti-radiation fillers and the urethane groups on the main chain of the water-based polyurethane to enhance the interfacial compatibility of the anti-radiation fillers and the water-based polyurethane, thereby increasing the loading capacity of the anti-radiation fillers in the composite coating and effectively improving the anti-radiation performance of the coating.

[0016] 2. The present application designs anti-radiation fillers with a core-shell structure, using high atomic number materials as the core layer to enhance Compton scattering, and combining a low atomic number shell layer to selectively absorb low-energy photons. At the same time, the electron density gradient at the core-shell interface can induce multiple reflections and scattering, prolonging the photon path and improving the attenuation probability, thereby improving the anti-radiation performance.

[0017] 3. The present application mechanically mixes modified anti-radiation fillers, water-based polyurethane emulsion and polyvinyl alcohol aqueous solution to prepare a water-based composite coating, which has a simple preparation process, is non-toxic and non-polluting, and has a significant impact of the loading capacity of the anti-radiation fillers on the mechanical properties and radiation shielding efficiency of the coating.

[0018] 4, The prepared water-based composite coating can be well attached on tinplate, aluminum 6061 alloy, fiber fabric and polystyrene plastic surface. Meanwhile, the composite coating has excellent thermal stability and mechanical properties. It can be used as radiation attenuation coating for the surface of equipment and fabric. BRIEF DESCRIPTION OF DRAWINGS

[0019] Figure 1 is a preparation process schematic diagram of the water-based composite coating with X / gamma ray attenuation performance of the present application;

[0020] Figure 2 (a) is the infrared spectrum diagram of the modified radiation protection filler before and after preparation, (b) is the X-ray diffraction diagram of the modified radiation protection filler before and after preparation, (c) is the transmission electron microscope and energy spectrum result of the modified gadolinium oxide filler, and (d) is the transmission electron microscope and energy spectrum result of the modified bismuth oxide filler.

[0021] Figure 3 is the infrared spectrum diagram of the water-based polyurethane and the water-based composite coating.

[0022] Figure 4 are the scanning electron microscope results of the water-based composite coating with the mass fraction of the modified radiation protection filler being 0 (a, b), 30% (c, d), 50% (e, f), and 70% (g, h), respectively.

[0023] Figure 5 (a) is the thermogravimetric curve of the water-based composite coating, Figure 5 (b) is the tensile curve of the water-based composite coating. WRAC0, WRAC30, WRAC50, and WRAC70 respectively represent the water-based composite coating with the mass fraction of the modified radiation protection filler being 0, 30%, 50%, and 70%

[0024] Figure 6 (a) is the X-ray shielding efficiency of the unmodified radiation protection filler control group, the water-based composite coating, and the simulation result, Figure 6 (b) is the gamma ray shielding efficiency of the unmodified radiation protection filler control group, the water-based composite coating, and the simulation result.

[0025] Figure 7 is the optical photograph of the water-based composite coating attached on tinplate, aluminum 6061 alloy, fiber fabric, and polystyrene plastic surface. DETAILED DESCRIPTION

[0026] The present application will be further described below in combination with the drawings and specific examples.

[0027] The preparation schematic diagram of the water-based composite coating with X / gamma ray attenuation performance of the present application is as shown in Figure 1The anionic waterborne polyurethane emulsion was prepared with polytetrahydrofuran and isophorone diisocyanate as monomers, 2,2-dimethylol butyric acid and 1,4-butanediol as chain extenders; the modified radiation protection filler with core-shell structure was prepared by ball milling with the assistance of tetraethyl orthosilicate; the polyvinyl alcohol was used to slow down the settlement of the filler, and the waterborne composite coating was prepared by mechanical mixing. The dispersion of the radiation protection filler was improved by the hydrogen bond interaction between the modified filler and the polyurethane, and the radiation attenuation ability was improved by the interface multiple scattering of the core-shell structure. The above multiple effects endow the composite coating with excellent thermal stability, mechanical properties and radiation attenuation performance. The infrared spectra of the modified radiation protection filler before and after preparation are shown in Figure 2 Fig. 1(a), the radiation protection fillers gadolinium oxide and bismuth oxide modified by tetraethyl orthosilicate have new characteristic peaks on the basis of retaining the original characteristic peaks, which indicates that the hydrolysis-condensation reaction of tetraethyl orthosilicate occurs under the catalysis of alkali, and a silica coating layer is successfully formed. As shown in Figure 2 Fig. 1(b), the X-ray diffraction results confirm that the synthesis process of the silica coating layer retains the chemical structure of the metal oxide core, and a large amount of amorphous silica shell is generated by the hydrolysis of tetraethyl orthosilicate. As shown in Figure 2 Figs. 1(c) and (d), the energy spectrum results can also confirm that the silica coating layer is successfully deposited on the surface of the radiation protection filler. The above results indicate the successful preparation of the modified radiation protection filler. Figure 3 Fig. 2 shows the infrared spectra of IPDI (isophorone diisocyanate), WPU (waterborne polyurethane) and WRAC (waterborne composite coating), and the infrared peaks of WRAC are slightly enhanced at 3340 cm -1 -1, the carbonyl characteristic peak is red shifted to 1699 cm -1 , and the C-O vibration peak is shifted to 1097 cm 1 , indicating that the modified filler is introduced and there is hydrogen bond interaction between the polyurethane matrix. The modified radiation protection filler can also achieve good dispersion at high load, and the scanning electron microscopy results are shown in Figure 4 Figs. 3(a) and (b). Figure 5 The thermal stability and mechanical properties are shown in Figs. 3(a) and (b), respectively. The hydrogen bond interaction between the hydroxyl sites on the surface of the modified filler and the polyurethane matrix enhances the thermal stability of the composite coating, and the thermal stability of the coating is enhanced with the increase of the load of the modified radiation protection filler. The interface bonding between the modified filler and the matrix is enhanced, so that there is better stress transfer between the filler and the matrix during the stretching process, and the composite coating has good ductility while the tensile strength is significantly improved. When the load of the radiation protection filler is 50%, the coating still has good flexibility, and only when the load is high (WRAC70) the flexibility will decrease. The radiation attenuation performance test is shown in Figure 6 Fig. 4, Figure 6 (a), the X-ray radiation source is 129I, with the increase of filler loading efficiency, the radiation attenuation efficiency of the composite coating also significantly improved, the radiation attenuation efficiency of 1.5mm thickness of WRAC70 can reach 99.1%. At the same time, the radiation attenuation efficiency of the composite coating is higher than that of the unmodified group and the simulation group, which is caused by the advantage of the material core-shell structure design. Figure 6 (b) the gamma-ray radiation source is 137 Cs, the radiation attenuation efficiency of 1.5mm thickness of WRAC70 is 5.10%, which is also higher than that of the unmodified group and the simulation result. Figure 7 It is shown that the composite coating can achieve good coating effect on a variety of substrates such as tinplate, aluminum 6061 alloy, fiber fabric and polystyrene.

[0028] Example 1:

[0029] 1) 10g of radiation protection filler was dispersed in a mixture of 160mL of ethanol and 10mL of water, ammonia was added to adjust the pH to 10, and the filler was uniformly dispersed in the solution under the action of ultrasonic wave for 20min. Then stir for 30min, add 0.67mL of ethyl silicate to assist ball milling for 6h. After ball milling, the product was washed with anhydrous ethanol by centrifugation for three times. Finally, the modified radiation protection filler was obtained by drying at 60℃.

[0030] 2) Polytetrahydrofuran (PTMG, 25.86g, 25.86mmol) and isophorone diisocyanate (IPDI, 14.2ml, 67.84mmol) were stirred at 80℃ under nitrogen protection for 1h; after cooling to 60℃, 2,2-dimethylol butyric acid (DMBA, 2.05g, 13.84mmol) and 1,4-butanediol (BDO, 1.67g, 18.53mmol) were added, and two drops of dibutyltin dilaurate were added dropwise, and the reaction was continued for 4h; then the system was cooled to 50℃, and triethylamine (TEA, 1.95ml, 13.84mmol) was added to neutralize the carboxyl groups on the polymer chain. During the reaction, 20% volume fraction of acetone was added to reduce the viscosity of the system. After 30min of neutralization, ice water bath was used for high-speed stirring while adding deionized water (DI, 81.4g) dropwise, and the stirring was continued for 1h. The acetone was removed by rotary evaporation to obtain a waterborne polyurethane emulsion with a solid content of about 30%.

[0031] 3) 1.5g of modified gadolinium oxide and bismuth oxide radiation protection filler prepared in step 1) was added to 20g of 7wt% polyvinyl alcohol aqueous solution, and ultrasonic stirring was carried out for 20min to obtain a smooth and uniform slurry. Then 18.67g of waterborne polyurethane emulsion was added, and after stirring for 30min, vacuum defoaming treatment was carried out, and the WRAC30 composite coating was obtained by casting into a customized fluorotetra mold and natural air drying.

[0032] The WRAC30 composite coating prepared in this example has an X-ray shielding efficiency of 77.3% and a gamma-ray shielding efficiency of 1.74%. It also has excellent thermal stability and mechanical properties.

[0033] Example 2:

[0034] 1) 10 g of the radiation protection filler was dispersed in a mixture of 160 mL of ethanol and 10 mL of water, and ammonia was added to adjust the pH to 10. The filler was uniformly dispersed in the solution under the action of ultrasonic waves for 25 min. Then it was stirred for 40 min, and 0.67 mL of tetraethyl orthosilicate was added for 6 h of ball milling. After ball milling, the product was washed three times by centrifugation with anhydrous ethanol. Finally, it was dried at 60°C to obtain the modified radiation protection filler.

[0035] 2) Polytetrahydrofuran (PTMG, 25.86 g, 25.86 mmol) and isophorone diisocyanate (IPDI, 14.2 ml, 67.84 mmol) were stirred at 80°C under nitrogen protection for 1 h; after cooling to 60°C, 2,2-dimethylol butyric acid (DMBA, 2.05 g, 13.84 mmol) and 1,4-butanediol (BDO, 1.67 g, 18.53 mmol) were added, and two drops of dibutyltin dilaurate were added dropwise, and the reaction was continued for 4 h; the system was cooled to 50°C, and then triethylamine (TEA, 1.95 ml, 13.84 mmol) was added to neutralize the carboxyl groups on the polymer chain. During the reaction, 30% volume fraction of acetone was added to reduce the viscosity of the system. After 30 min of neutralization, ice water bath was used for high-speed stirring while adding deionized water (DI, 81.4 g) dropwise, and the stirring was continued for 1 h. Acetone was removed by rotary evaporation to obtain a waterborne polyurethane emulsion with a solid content of about 30%.

[0036] 3) 2.5 g of the modified gadolinium oxide and bismuth oxide radiation protection filler prepared in step 1) was added to 14.29 g of a 7 wt% mass concentration polyvinyl alcohol aqueous solution, and ultrasonic stirring was performed for 25 min to obtain a smooth and uniform slurry. Then 13.33 g of the waterborne polyurethane emulsion was added, and after stirring for 35 min, vacuum defoaming treatment was performed. The WRAC50 composite coating was obtained by casting into a customized fluorotetra mold and natural air drying.

[0037] The WRAC30 composite coating prepared in this example has an X-ray shielding efficiency of 89.0% and a gamma-ray shielding efficiency of 2.81%. It also has excellent thermal stability and mechanical properties.

[0038] Example 3:

[0039] 1) 10 g of the anti-radiation filler was dispersed in a mixed solution of 160 mL of ethanol and 10 mL of water, and ammonia water was added to adjust the pH to 10. The filler was uniformly dispersed in the solution under the action of ultrasonic waves for 30 min. Then it was stirred for 60 min, and 0.67 mL of tetraethyl orthosilicate was added to assist ball milling for 6 h. After ball milling, the product was washed by centrifugation with anhydrous ethanol three times. Finally, it was dried at 60°C to obtain the modified anti-radiation filler.

[0040] 2) Polytetrahydrofuran (PTMG, 25.86 g, 25.86 mmol) and isophorone diisocyanate (IPDI, 14.2 ml, 67.84 mmol) were stirred at 80°C under nitrogen protection for 1 h; after cooling to 60°C, 2,2-dimethylol butyric acid (DMBA, 2.05 g, 13.84 mmol) and 1,4-butanediol (BDO, 1.67 g, 18.53 mmol) were added, and two drops of dibutyltin dilaurate were added dropwise, and the reaction was continued for 4 h; the system was cooled to 50°C, and then triethylamine (TEA, 1.95 ml, 13.84 mmol) was added to neutralize the carboxyl groups on the polymer chain. During the reaction, 40% volume fraction of acetone was added to reduce the viscosity of the system. After 30 min of neutralization, ice water bath was used for high-speed stirring while adding deionized water (DI, 81.4 g) dropwise, and the stirring was continued for 1 h. Acetone was removed by rotary evaporation to obtain a waterborne polyurethane emulsion with a solid content of about 30%.

[0041] 3) 3.5 g of the modified gadolinium oxide and bismuth oxide anti-radiation filler prepared in step 1) was added to 8.57 g of a 7 wt% polyvinyl alcohol aqueous solution, and ultrasonic stirring was performed for 30 min to obtain a smooth and uniform slurry. Then 8 g of the waterborne polyurethane emulsion was added, and after stirring for 40 min, vacuum defoaming treatment was performed, and the WRAC70 composite coating was obtained by casting into a customized fluorotetra mold and natural air drying.

[0042] The X-ray shielding efficiency of the WRAC30 composite coating prepared in this example was 99.1%, and the γ-ray shielding efficiency was 5.10%. It also had excellent thermal stability and mechanical properties.

Claims

1. A method for preparing a water-based composite coating with X / γ-ray attenuation properties, characterized in that: The composite coating utilizes hydrogen bonding interactions between hydroxyl groups on the surface of a modified radiation-proof filler and urethane groups on the main chain of a waterborne polyurethane to achieve high-load dispersion. The modified radiation-proof filler has a core-shell structure, which can increase the mean free path of incident photons, thereby improving radiation protection performance. The preparation method of the waterborne composite coating specifically comprises the following steps: (1) Preparation of modified radiation-proof filler: The radiation-proof filler is dispersed in a mixed solution of ethanol and water, ammonia water is added to adjust the pH to 10, and the radiation-proof filler is uniformly dispersed in the solution under ultrasonic action for 20 to 30 minutes; then, the mixture is stirred for 30 to 60 minutes, and then ethyl orthosilicate is added and ball-milled for 6 hours; the ball-milled product is centrifuged and washed several times with anhydrous ethanol; and finally, the mixture is dried at 60°C to obtain the modified radiation-proof filler. (2) Preparation of waterborne polyurethane emulsion: Polytetrahydrofuran and isophorone diisocyanate were stirred and reacted at 80°C under nitrogen for 1 hour; after cooling to 60°C, 2,2-dihydroxymethylbutyric acid and 1,4-butanediol were added, and 1-3 drops of dibutyltin dilaurate were added dropwise, and the reaction was continued for 4 hours; the reaction system was cooled to 50°C, and then triethylamine was added to neutralize the carboxyl groups on the polymer chain; during the entire reaction process, 20-40% volume fraction of acetone was added to reduce the viscosity of the system; after neutralization for 30 minutes, deionized water was added dropwise while stirring at 600-800 rpm in an ice-water bath, and then stirring was continued at the same speed for 1 hour. The acetone was removed by rotary evaporation to obtain a waterborne polyurethane emulsion; (3) Preparation of composite coating: The modified radiation-proof filler prepared in step (1) is added to a polyvinyl alcohol aqueous solution and ultrasonically stirred for 20 to 30 minutes to obtain a smooth and uniform slurry; then the aqueous polyurethane emulsion prepared in step (2) is added to the slurry, stirred for 30 to 40 minutes, and then vacuum defoamed to obtain a water-based composite coating.

2. The method for preparing a water-based composite coating with X / γ-ray attenuation performance according to claim 1, characterized in that: The radiation-proof filler in step (1) is at least one of bismuth oxide and gadolinium oxide.

3. The method for preparing a water-based composite coating with X / γ-ray attenuation performance according to claim 1, characterized in that: The mass ratio of the radiation-proof filler to ethyl orthosilicate in step (1) is 15:1-10.

4. The method for preparing a water-based composite coating with X / γ-ray attenuation properties according to claim 1, characterized in that: In step (2), the molar ratio of isocyanate groups to total hydroxyl groups is 1.15 to 1.

25.

5. The method for preparing a water-based composite coating with X / γ-ray attenuation performance according to claim 1, characterized in that: The mass fraction of 2,2-dihydroxymethylbutyric acid in the whole reaction system in step (2) is 4.5-5%.

6. The method for preparing a water-based composite coating with X / γ-ray attenuation properties according to claim 1, characterized in that: The mass concentration of the polyvinyl alcohol aqueous solution in step (3) is 5-7%.

7. The method for preparing a water-based composite coating with X / γ-ray attenuation properties according to claim 1, characterized in that: The mass fraction of the radiation-proof filler in the water-based composite coating in step (3) is 7-36%, the mass fraction of the polyvinyl alcohol aqueous solution is 44-48%, and the mass fraction of the water-based polyurethane emulsion is 20-45%.

8. A water-based composite coating with X / γ-ray attenuation properties, characterized in that: The method is prepared by the method according to any one of claims 1 to 7.